Fertility following progesterone induced estrus in Murrah buffaloes* - Chhatry, Usha; Pandit, R K; Agrawal, R G (The Indian Journal of Animal Sciences, 2012)
Murrah buffaloes (60) were studied during the breeding (November to February) and low breeding (March to June) seasons in 6 groups with equal numbers of animals in each. During the breeding season a group of anestrus buffaloes was treated with short·term synthetic progesterone ear implant. There were 2 untreated control groups including anestrus and normal cycling buffaloes. Similarly, during the low breeding season also the same treatment was repeated. There was a significant variation (P < 0.05) in minimum/maximum environmental temperature during breeding (13.15±1.2/24.9±1.45°C) and low breeding (22.37±2.9 / 36.4±2.5 °C) season. Similarly, the minimum / maximum humidity during the breeding (54.75±7.04/89.75± 1.65 %) and low breeding (29.25±4.73 / 62.75±5.35 %) seasons varied significantly (P < 0.05). The estrus response following the progesterone ear implant insertion was better during the breeding (80.00 %) than the low breeding season (60.00 %), but there was no significant difference in estrus induction time during the breeding (62.8±10.4 hr) and low breeding (63.2±8.70 hr) seasons. However, the first service conception rate was better (70.00 %) during the breeding than the low breeding season (30.00 %). In good to satisfactory arborization pattern, the conception rate was higher during breeding (77.77 %) than the low breeding season (50.00 %). When no arborization pattern was seen the conception rate was nil in both the seasons. The pre-/post- progesterone treated values of calcium (9.7±0.25 / 12.33±0.44 mg ( 100 ml), zinc (214.6±13.52/ 302.14± 17.59mg /100 ml) and iron (143.85±14.57 /160.07±7.87 mg / 100 ml) were elevated highly significantly (P < 0.05) whereas the rise in manganese (3.5±0.48 / 4.11±0.95µg/ml) was significant.